Sharing and jumping task design on chemical equilibrium lesson for improving learning quality at senior high school - W Nurningsari; A Supriatna; S Hendayana (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Lack of teacher anticipation of students responses lead to obstacles in a learning process which affect the quality of learning, therefore we need develop an innovation of learning design that has prediction of student’s response. The purpose of this research is to develop didactical design based on sharing and jumping task in chemical equilibrium calculation. Sharing task used to facilitate students slow learners with help fast learners. While jumping task used to challenge fast learners so they didn’t feel bored in learning. The method used in this research is the Didactical DesignResearch (DDR), which consists of three stages: prospective analysis, metapedadidactical, and retrospective analysis. The developed didactical design was implemented at students of grade 11 of a senior high school in Bandung. Then the revised didactical design was implemented at another group of students of grade 11. Data was collected through observations, interviews, documentation, then the data is transcribed and analyzed. Based upon the result of the first implementation analysis it was found that the teacher still dominated the learning proses, but in the second implementation of the revised didactical design affected some changes in the learning process indicated some students have started to discuss actively.